DESIGN AND IMPLEMENTATION OF WEB-BASED REGISTRATION SYSTEM IN KLINIK MEDIKA ANTAPANI BANDUNG USING BLACK BOX TESTING - Eris Dwi Purnama; Fierzha Anugrah Putra (Jurnal Ilmiah Sistem Informasi, 2022)
Klinik Medika Antapani is a business entity that serves the community in providing public health services for the community. Currently the patient registration process at Klinik Medika Antapani still uses a stand-alone desktop based application with Microsoft access which still causes queues in the registration section and through conventional registration via Whatsapp. An information system is needed to implement a more effective and efficient service concept at Klinik Medika Antapani. Web-based patient registration applications is one of the best suitable sollution for implemented in Klinik Medika Antapani.  Web-based Patient registration application are way more easier to access because they only require a LAN or WAN internet connection and can be accessed directly without having to install the application to the computer. This Web Based Registration System will be very effective if implemented in Klinik Medika Antapani which is still based on onsite registration and manual registration through Whatsapp.